Kondisi Sanitasi Dasar di Wilayah Pesisir Moramo Utara, Kabupaten Konawe Selatan - Listy Handayani; Jusniar Rusli Afa; Nurhijrianti Akib (Program Studi S2 Kesehatan Masyarakat Universitas Halu Oleo, 2025)
Basic sanitation is an effort to improve public health by ensuring clean and healthy environmental conditions. Coastal areas are known to face unique challenges, problems and opportunities in the health sector, especially environmental sanitation, compared to other regions. The study aims to determine the basic sanitation conditions in the coastal area of ​​North Moramo, South Konawe District in 2024. The type of this study is descriptive observational which was carried out in the coastal area of ​​North Moramo, especially Wawatu Village in July 2024. The sample was 100 respondents determined using techniques accidental sampling. Data collection by filling out questionnaires and observation sheets then analyzed univariately using a computer program. The results showed that majority of respondents used refilled water as the main source of drinking water without processing it. In addition, they used private septic tank latrines. Garbage is disposed of in landfills in open containers and processed by burning it. Disposal of waste water, the majority of respondents have disposed of their waste in the waste water disposal channel. Thus, it is hoped that the coastal communities of North Moramo need to treat their water first before drinking, use closed and watertight trash containers and not burn rubbish.